30 years of Information Research papers citing Professor Tom D. Wilson: a bibliometric analysis - Svarre, Tanja; Larsen, Birger (Information Research an international electronic journal, 2025)
Introduction. As part of the Information Research jubilee, we present an analysis of Professor Tom D. Wilson’s impact on the journal from a citation and bibliometric perspective. Method. Using Scopus, we identified Information Research papers that cite Wilson. We carried out a cluster analysis based on bibliographic coupling in VOSviewer and created a map showing the interrelationships between the papers and their resulting seven clusters. We then used ChatGPT to identify the themes of the clusters and finally compared citations to Wilson’s most cited works in Information Research and Scopus. Results. The analysis shows how Wilson’s papers have contributed to a wide variety of studies with a focus on information behaviour. Papers cited in Information Research range from reviews to empirical work, and from health information to social media, as well as emotional and organisational perspectives on the use of information. Conclusions. The variety of papers identified in seven clusters through the analysis illustrates the core role of Wilson’s work, as an editor of Information Research, and as a researcher of information behaviour.